(3Mbhb GdZjQ aj GdYbhO GdeGdjI aj Gdabg GdESdGej hGdbGfhf GdhVYj (B/s - (3HhOj, MSf eMeOs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYI GdLOjOI ddfTQ(B, s, 2004)
(3GdZjQ hJYdb Mbhbg HGdYbO GdeGdj(B- (3eaghe GdZjQ(B- (3GdYbO GdeGdj hMbhb GdZjQ ajg(B- (3GdMbhb GdYjfjI ddZjQ aj GdYbO GdeGdj(B- (3GdMbhb GdYjfjI GdJGeI(B- (3Mb GdeGdc aj GdJYGbO GdaVhdj(B- (3Mb GdeGdc aj GSJMbGb GdYbO GdeGdj GdeJQJH Ydi edcg HJYOj(B- (3GdMbhb GdYjfjI ZjQ GdJGeI(B- (3GdMbhb GdTNUjI GdeJYdbI HeMd GdYbOs
Keywords: (3GdEbJUGO GdESdGejs; (3GdYbhOs; (3GdYbhO GdeGdjIs